Penilaian Kinerja Karyawan Menggunakan Metode Simple Multi Attribute Rating Technique (SMART) - Fransiskus Panca Juniawan; Dwi Yuny Sylfania; Robbi Rahim (Ikatan Ahli Informatika Indonesia, 2021)
Employee performance assesment is one aspect that must be considered to achieve the goals of an institution. With the application of information technology, a decision support system can be used to provide an assessment. Currently, there are many methods that can be used to assess employee performance. One of them is the SMART (Simple Multi Attribute Rating Technique) method. This method was chosen because of its advantages that able to solve problems using multicriteria so it is suitable for determining the employee performance assessment of an institution. The criteria used in the assessment are also important in determining the performance assesment. There are many criteria that can be used in determining employee performance assessment. In this study used five criteria, namely Discipline, Work Motivation, Responsibility, Leadership and Honesty. The research method used consists of the needs identification stage, needs analysis, SMART method analysis, and implementation in the form of testing the results of manual calculations applied to a web-based system. The calculation uses data from seven employees using five criteria. From the results of the tests carried out, it is known that the results of manual calculations are the same as the web system.